Investigation of mechanical and wear characteristic of Banana/Jute fiber composite. (2021) - Suresh, A.; Jayakumar, L.; Devaraju, A.
Abstract: Nowadays, Organic fiber composites are utilized in different designing applications to expand the quality, upgrade the carrying load, and reduce the product cost. Untreated banana and jute fiber are taken to develop a hybrid natural composite for the current investigation. The specimen was produced using epoxy resin-LY556 as the matrix content and HY951 as hardener in compliance with the ASTM D-3039 / D-256 specification. The fibers are randomly chocked fiber using the hand-layup manufacturing technique. The wear tests were performed using an ASTM-G99 standard Pin-on - Disk wear tester. Wear test performed on prepared standard specimen with different percentages. It utilized to locate the most significant parameter that impacts the reactions. The outcomes showed that the applied load fundamentally impacts the reactions contrasted with sliding velocity and sliding distance.